2022
DOI: 10.3390/axioms11110581
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Share of Solar Power in China Based on FGM (1,1) Model

Abstract: In recent years, fossil energy reserves have decreased year by year, and the development and use of renewable energy has attracted great attention of governments all over the world. China continues to promote the high-quality development of renewable energy such as solar power generation. Accurate prediction of the share of solar power in China is beneficial to implementing the goals of carbon peaking and carbon neutralization. According to the website of China’s National Bureau of statistics, the earliest ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This was modeled on Germany's Renewable Energy Act of 2000, which used a feed-in tariff policy for solar power generation. Li, Wang, Dai, and Wu [28] showed that the Chinese government's support for the solar energy industry has given a strong impetus to the development of solar power generation.…”
Section: Renewable Energymentioning
confidence: 99%
“…This was modeled on Germany's Renewable Energy Act of 2000, which used a feed-in tariff policy for solar power generation. Li, Wang, Dai, and Wu [28] showed that the Chinese government's support for the solar energy industry has given a strong impetus to the development of solar power generation.…”
Section: Renewable Energymentioning
confidence: 99%
“…The specific weight allocation is calculated using fractional order, which can be determined using heuristic algorithms. Currently, the FGM(1,1) model has been widely utilized for various predictions, including energy consumption, environmental quality [20][21][22][23][24], express delivery business volume [25], the added value of high-tech industries [26], and the total output value of China's construction industry [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the defects existing in the precision of the model, Wu et al [29] introduced the concept of fractional order into the grey sequence operator and grey forecasting model [30] and developed the FGM (1,1). In this model, every sequence is multiplied by a distinct fractional order [27,31]. This model has been successfully implemented in energy consumption prediction [32], carbon sink capability prediction [33], and other fields.…”
Section: Introductionmentioning
confidence: 99%